Peran Manajemen Keselamatan Kapal, Keterampilan Crew dan Kemampuan Berkomunikasi dalam Meningkatkan Keselamatan Pelayaran pada Kapal Persada Utama 9 - Agus S, Tri; Rumambi, Freddy J.; Tangkudung, Auderey G. Dotulong; Rudianto, Rudianto (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to determine the role of ship safety management, crew skills, and communication skills in improving navigational safety on the Persada Utama 9 ship. A qualitative research method was employed using in-depth interviews with crew members and ship management. The findings reveal that the implementation of the International Safety Management (ISM) Code and Safety of Life at Sea (SOLAS) conventions has been carried out through routine inspections, internal audits, and the provision of safety equipment. However, the implementation remains suboptimal due to weaknesses in incident reporting, emergency drill execution, and periodic training. Furthermore, crew competencies, both technical and non-technical, still require improvement, particularly in operating safety equipment, using modern navigation systems, and making decisions under pressure. Communication challenges were also identified, especially in the use of maritime English and Standard Marine Communication Phrases (SMCP). The study emphasizes that maritime safety does not merely depend on administrative compliance with international regulations but also requires the strengthening of safety culture, continuous capacity building for crew members, and the development of effective communication